2021
DOI: 10.1371/journal.pone.0253746
|View full text |Cite
|
Sign up to set email alerts
|

Treatment seeking delay and associated factors among tuberculosis patients attending health facility in Ethiopia from 2000 to 2020: A systematic review and meta analysis

Abstract: Background Treatment seeking delay is defined as the time interval between the onset of the major symptoms of tuberculosis (TB) and the first visit to the formal health care facility. The patient was said to be delayed if the patient visited the health-facility after 3 weeks onset of major symptoms. However, in low-income countries like Ethiopia, the delay in treatment-seeking among tuberculosis patients contributes to a widespread transmission and high prevalence of tuberculosis. Methods Studies were retrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 54 publications
0
17
2
Order By: Relevance
“…Therefore, measures should be taken to improve TB-related attitudes and behaviours among the elderly, which may help to increase willingness to seek medical care for TB. Intriguingly, we found that TB knowledge scores were not a significant determinant of willingness to seek medical care in the multivariate analysis, which was not in line with previous studies 9 25 26 32 39. Therefore, the association between TB knowledge and willingness to seek medical care needs further research.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Therefore, measures should be taken to improve TB-related attitudes and behaviours among the elderly, which may help to increase willingness to seek medical care for TB. Intriguingly, we found that TB knowledge scores were not a significant determinant of willingness to seek medical care in the multivariate analysis, which was not in line with previous studies 9 25 26 32 39. Therefore, the association between TB knowledge and willingness to seek medical care needs further research.…”
Section: Discussioncontrasting
confidence: 96%
“…[23][24][25] In addition, unwillingness to seek medical care may increase the potential risk of transmission and will have a negative impact on their families and society. 26 Our findings showed that the main reason for being unwilling to seek medical care for TB was 'long treatment cycle and heavy economic burden'. This indicated that individuals' economic situation impacts their willingness to seek treatment.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Despite the advance in diagnosis and expansion of TB services, patients’ poor health-seeking behaviour and diagnostic delay of EPTB cases remained problematic in Ethiopia and the case-detection efforts are unsuccessful and TB is very widespread in the country [ 18 , 19 ]. Many community-based studies reported that the number of undetected EPTB cases in communities can be greater than the number of notified cases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%